National Health Emergency Plan: A framework for the health and disability sector - Johal SS; MacDonald C; Mitchell J (Ministry of Health)
This edition of the National Health Emergency Plan has been revised and updated to reflect current thinking on the health aspects of emergency management in New Zealand and internationally. It reflects the sophistication of a second-generation, risk-based plan developed by emergency management specialists under the leadership of the Joint Centre for Disaster Research in partnership with the Ministry of Health. The plan was developed in consultation with local and international specialists in the field of emergency management, emergency managers and planners in the health and disability sector, and other key stakeholders. A collaborative, consultative approach has been taken throughout the development of the plan, including holding workshops with health emergency management stakeholders across the nation. Constant contact has been maintained with the concurrent review of the National Civil Defence Emergency Management Plan Order 2015 (National CDEM Plan) to ensure consistency between the two plans. In acknowledgement of the importance of evidence-based policy and practice, an extensive international literature review formed the basis for much of the plan’s content. To maintain its alignment with the National CDEM Plan, the National Health Emergency Plan will be reviewed by the Ministry of Health within five years of its adoption. The plan will also be reviewed and updated as required following any new developments or substantial changes to the operations or organisation of New Zealand health and disability services, as a result of lessons from a significant emergency affecting the health of communities or the health and disability sector itself, if new hazards and risks are identified, or by direction of the Minister of Health or Director-General of Health. Annexes at the back of the plan are intended to provide a short document format that can be rapidly updated with new or revised guidance on specific issues as they are identified. The Ministry of Health welcomes submissions of good practice that can be incorporated into future editions.